COMPARISON OF ANTIMICROBIAL EFFICACY OF HONEY GEL AND CLOTRIMAZOLE CREAM IN THE TREATMENT OF VULVOVAGINAL CANDIDIASIS SYMPTOMS - Arif Rahman Nurdianto; Heryanti Pusparisa; Hotimah Masdan Salim; Joko Sulistyo (STIKES Rumah Sakit Anwar Medika, 2022)
The available literature regarding the epidemiological or clinical features of vulvovaginal candidiasis (VVC) in most women will experience episodes of vulvovaginal candidiasis in their lifetime, 50% of whom will experience at least a second episode, and 5-10% of all women will experience recurrent vulvovaginal candidiasis (≥ 4 episode / 1 year). Vulvovaginal candidiasis is known as one of the most common yeast infections in women of reproductive age and is considered an important public health problem. In recent years, due to resistance to common antifungal drugs, the use of traditional antifungal medicines and herbal remedies has increased. Therefore this system aimed to investigate the effect of honey vaginal gel/ointment and to compare it with clotrimazole vaginal cream on symptoms of vulvovaginal candidiasis in patients. Vaginal clotrimazole is the drug of choice for the treatment of VVC. However, the increasing drug resistance to these microorganisms has led to greater interest in naturally occurring antifungal drugs. This systematic literature was conducted to compare vaginal honey ointment/gel and clotrimazole vaginal cream for the treatment of VVC.